Integrating Islamic Educational Programs for Street Children in Central Java: A Contextual Analysis - Imam Suyuti; Wahyu Kholis Prihantoro; Aida Hayani; Rizal Fathurrohman; Muhammad Gafarurrozi; Ahmad Salim; Farida Musyrifah (STAI Hubbulwathan Duri, 2024)
Street children in Central Java, Indonesia, often experience severe socio-economic challenges such as poverty, family instability, and a lack of social support, which lead to vulnerability to exploitation and abuse. This study explores the impact of Islamic educational interventions on improving their well-being and integration. A qualitative case study approach was used, with data collected from January to June 2024 through semi-structured interviews, participant observations, focus group discussions, and document analysis across three locations in Semarang. The study included 30 participants, including both current and senior members of Majelis Mafia Sholawat, tutors, mentors, and group leaders. Findings indicate that Islamic education initiatives enhance reasoning, moral development, emotional well-being, and self-awareness among street children. These programs adopt a holistic approach, addressing emotional, spiritual, and practical needs, and foster a sense of community and belonging. The study highlights the effectiveness of culturally sensitive educational strategies in promoting socio-economic opportunities and social integration for street children. The inclusion of community-centered, religious-based education appears crucial in addressing the unique challenges faced by these children. The findings suggest that policymakers and educators should consider culturally relevant educational programs that integrate local languages, customs, mentorship, and life skills training. Such initiatives can promote sustained engagement, improve socio-economic prospects, and support the overall integration of street children into society.